2013
DOI: 10.1093/geront/gnt040
|View full text |Cite
|
Sign up to set email alerts
|

Positive Affect Is Associated With Fewer Sleep Problems in Older Caregivers but not Noncaregivers

Abstract: Results suggest that routine screening and interventions to increase PA may reduce sleep problems among older caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…The premise of positive psychological well-being includes the notion that improved well-being will be accompanied by the optimal functioning of the persons' physiological systems (Phelan et al 2010;Ryff et al 2004). Also research has indicated that individuals who are high in components of psychological well-being other than purpose in life such as positive affect have fewer physical symptoms and better overall health (Fredman et al 2014). Research by Ancoli-Isreal suggests a strong association between sleep difficulties and cardiac disease (Ancoli-Israel 2009), this research also posits that comorbidities associated with aging, such as medical and psychiatric illness, like cardiac disease and depression, foster the decreased ability to sleep in older adults rather than increasing age alone.…”
Section: Discussionmentioning
confidence: 99%
“…The premise of positive psychological well-being includes the notion that improved well-being will be accompanied by the optimal functioning of the persons' physiological systems (Phelan et al 2010;Ryff et al 2004). Also research has indicated that individuals who are high in components of psychological well-being other than purpose in life such as positive affect have fewer physical symptoms and better overall health (Fredman et al 2014). Research by Ancoli-Isreal suggests a strong association between sleep difficulties and cardiac disease (Ancoli-Israel 2009), this research also posits that comorbidities associated with aging, such as medical and psychiatric illness, like cardiac disease and depression, foster the decreased ability to sleep in older adults rather than increasing age alone.…”
Section: Discussionmentioning
confidence: 99%
“…The age limit used to designate caregivers in studies analyzed in present review was in 35.3% of the cases ≥ 60 years 17,18,24,27,31,32 and in 29.4% ≥ 65 years 20,21,23,28,33 . Three texts (17.6%) did not mention any limit, but in results it was possible to see all caregivers were older adults 22,25,30 .…”
Section: Search On Databases Lilacs N = 34mentioning
confidence: 99%
“…By analyzing the articles' results it was possible to see that 52.9% evaluated only familiar caregiver 17,[20][21][22]25,[29][30][31][32] and in 47.1% caregiver could be even familiar or not 18,19,23,24,[26][27][28]33 .…”
Section: Search On Databases Lilacs N = 34mentioning
confidence: 99%
See 2 more Smart Citations